2008
DOI: 10.2215/cjn.02490508
|View full text |Cite
|
Sign up to set email alerts
|

Association of Visceral and Subcutaneous Adiposity with Kidney Function

Abstract: Background and objectives: Obesity is a risk factor for incident chronic kidney disease (CKD). Visceral (VAT) and subcutaneous adipose tissue (SAT) may confer differential metabolic risk profiles. The relations of VAT and SAT were analyzed with CKD as estimated by creatinine-and cystatin-based estimating equations.Design, setting, participants, & measurements: Participants from the Framingham Offspring Study who underwent abdominal computed tomography for VAT and SAT quantification were included (n ‫؍‬ 1299; 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 42 publications
2
44
2
2
Order By: Relevance
“…a Analysis is performed on log-transformed data. adiposity is associated with the incidence of CKD [31,32]. Our data show that the risk for abnormal albuminuria and CKD increases by 68% and 54% per 1 SD increase in IHTG content, which is independent of traditional cardio-metabolic risk factors, including insulin resistance, metabolic syndrome, and abdominal visceral fat.…”
Section: Discussionmentioning
confidence: 57%
“…a Analysis is performed on log-transformed data. adiposity is associated with the incidence of CKD [31,32]. Our data show that the risk for abnormal albuminuria and CKD increases by 68% and 54% per 1 SD increase in IHTG content, which is independent of traditional cardio-metabolic risk factors, including insulin resistance, metabolic syndrome, and abdominal visceral fat.…”
Section: Discussionmentioning
confidence: 57%
“…51 In this cohort with a mean age of 60±9 years, the prevalence of CKD (GFRo60 ml min À1 per 1.73 m 2 ) was 6.8% using MDRD GFR and 10.5% using cystatin C-based GFR. There was no association between visceral adipose tissue and subcutaneous adipose tissue and CKD as defined by MDRD as there was for cystatin-based equations.…”
Section: à2mentioning
confidence: 70%
“…Obesity is an independent risk factor for renal impairment, as showed by Chen et al (20) who reported that the risk for CKD was more than twice as high in patients with increased WC than in those without increased WC. Furthermore, Young et al (21) found that visceral and subcutaneous adipose tissue (as measured by computed tomography) were associated with CKD defined only with cystatin C estimating equations, but not when using a creatinine-based estimating equations.…”
Section: Discussionmentioning
confidence: 99%